Category Membership: Suatu Pendekatan Analisis Positioning pada Food Convenience Retail di Jakarta - Fortunisa, Ananda; Trihartanto, Bambang (Business and Management Review, 2012)
Category membership is a brand of excellence and functionality of a closest substitute product. In this case,marketers sort product attributes or benefits into two points, point of parity and point of difference, in order to formthe frame of reference of the product. Frame of reference can help marketers to find out who its competitors are andwhere to position himself in the membership category. This study aims to examine the factors forming the 7-Eleven 'spositioning and to determine 7-Eleven 's category membership in the retail business in Indonesia. Both of these isvery important to investigate, because 7-Eleven is not nor in convenience store neither in food store anyway. Thisstudy uses descriptive method verification, which is implemented through field data collection by distributingquestionnaires to 150 respondents in three outlets, Matraman, Plaza Festival, and Farnan Menteng. Respondentswere selected at 1;andom, and who had been shopping at 7-Eleven. Based on the perspective of the respondents, theresults showed that 7-Eleven is not clearly in the group membership categories, whether in the category ofcommodities business retailer or restaurant services retailer. This is because although 7 -Eleven has a patented foodproduct but 7-Eleven also sells merchandise day-to-day needs. The results suggest that 7-Eleven has to morefocusing in what types of retailer category, so it was able to under,stand who its competitors and how to deal with it.Keyword: category membership, positioning, food-convenience retail DAFTAR PUSTAKA Aaker, D.A., & Shansby, G.J. 1982. Positioning Your Product. Business Horizons, Vol. 25 May/June, pp.56-62. Ander, W.N. and Stern, N.Z. 2005. Winning at Retail. Beijing : Publishing House of Electronics Industry. Anderson, J.R. and Bower, G.H. 1973.  Human Associative Memory. Washington DC : Winston & Sons. Collier, David A., and Meyer, Susan M. 1995. A Service Positioning Matrix. International Journal of Operations & Production Management. Vol. 18 No. 12. pp. 1223-1244. Crawford, F. and Matthew, R. 2002. The Myth of Excellence. Beijing: China Citic Press. Deese, J. 1965.  The Structure of Associatiations in Languange and Thought. Baltimore. MD : John Hopkins Press. Dillon, W.R., Domzal, V. and Madden, T.J. 1986. Evaluating Alternative Product positioning strategies. Journal of Advertising Research. August/September, pp. 29-35. Fei, Li., Bu, Mi., Gao, Wang., and Xiang, Li. 2010. An Empirical Study on the Positioning Point of Successful Retail Enterprises in China. Nankai Business Review International Vol. 1 No. 2, pp. 152-165. Freud, S. 1924.  Collected Papers. London: Hogarth. Fuchs, Christoph., &  Diamantopoulos, Adamantios. 2010 Evaluating the Effectiveness of Brand-Positioning Strategies from Consumer Perspective. European Journal of Marketing Vol. 44 No. 11/12, 2010 pp. 1763-1786 . Galton, F. 1880. Psychometric Experiments. Brain. Vol. 2. Pp. 149 – 62. Javalgi, Rajshekhar (Raj) G., Joseph, W. Benoy.,  and Gombeski, William R. Jr. 1995. Positioning Your Service to Target Key Buying Influences: The Case of Referring Physicians and Hospitals. Journal of Services Marketing Vol. 9 No. 5 1995 pp. 42-52. Kalafatis, P. Stavros., Tsogas, Margos H., & Blankson, Charles. 2000. Positioning Strategies in Business Markets. MCB University Press : Journal of Business & Industrial Marketing, Vol 15 No. 62000, pp. 416-437. Kalra, A., & Goodstein, R.C. 1998. The Impact of Advertising Positioning Strategies on Consumer Price Sensitivity. Journal of Marketing Research. Vol. 35 No.May, pp.210-24. Keller, K.L. & Lehmann, D.R. 2006. Brands and Branding: Research Findings and Future Priorities. Marketing Science, Vol. 25 No. 6, pp. 740-59. Keyt, John C., Yavas, Ugur and Riecken, Glen. 1995. Importance-Performance Analysis A Case Study in Restaurant Positioning. International Journal of Retail & Distribution Management, Vol. 22. No. 5. pp. 35-40 Kotler, Philip & Amstrong, Gary. 2008. Prinsip-prinsip Pemasaran. Edisi 12. Jakarta : Erlangga. Kotler, Philip. 2000. Marketing Management. New Jersey : Prentice Hall. Kotler, Philip. 2003. Marketing Management. New Jersey : 11th ed. Pearson Prentice-Hall. Upper Saddle River. Levy, Michael & Weitz, Barton A. 2007. Retailing Management. New York : McGraw-Hill Irwin. Lusch, Robert., Dunne, Patrick M., & Carver, James R. 2011. Introduction to Retailing. South-Western : Cengage Learning. Marsden, P. 2000. The Werther Effect. Doctoral Thesis. Brighton: University of Sussex. Nasir, Moh. 1999. Metode Penelitian. Cetakan Keempat. Jakarta: Ghalia Indonesia. h 63. Pham, M.T., & Muthukrishnan, A.V. 2002. Search and Alignment in Judgment Revisions: Implications for Brand Positioning. Journal of Marketing Research, Vol. 39 No.1, pp.18-30. Philip., Keller, Kevin Lane., Koshy, Abraham., Jha, Mithileshwar. 2010. Crafting the Brand Positioning. http://www.mdi-marquity.com [diakses 12 Juli 2011]. Ries, A.L. and Trout, J. 1986.  Positioning: The Battle for your Mind. London : McGraw-Hill. Simamora, Bilson. 2004. Riset Pemasaran: Falsafah, Teori, dan Aplikasi. Jakarta : PT. Gramedia Pustaka Utama. h 88 – 120 dan 231. Szalay, L. and Deese, J. 1978.  Subjective Meaning and Culture: An Assessment through Word Associations. Hillsdale, NJ : Lawrence Erlbaum Associates. Wagner, W., Valencia, J. and Elejabarrieta, F. 1996.  Relevance Discourse and The ‘Hot’ Stable Core of Social Representations: A Structural Analysis of Word Associations.  British Journal of Social Psychology, Vol. 35, pp. 331-52. http://corp.7-eleven.com/NewsRoom/2009. 7-Eleven, Inc. Partners with PT. Modern Putraindonesia in Master Franchise for 7 Eleven® Stores in Indonesia. [7 Maret 2011]